Pengaruh Dinamika Kelompok Sosial Terhadap Angka Kejadian Dan Penyembuhan Penyakit Tuberkulosis Paru Di Wilayah Puskesmas Mojoroto - Pardjono Pardjono; Puguh Santoso; Dyah Ika Krisnawati; Erna Susilowati; Elfi Quyumi; Novita Setyowati (coba, 2012)
Pulmonary tuberculosis is a chronic disease that must be controlled through a comprehensive program to achieve Indonesian Health Program in 2012. From retrospective data recorded and reported, tuberculosis (Pulmonary Tuberculosis) is one of the cases that should get routine examination and scheduled to visit health center. Public Health Center activities to the TB’s patient are by promotive, preventive, rehabilitative, and curatif coordinate with activities in the development of health centers The purpose of this study was to determine the effect of social group dynamics of events and healing tuberculosis lung disease in Public Health Center Mojoroto. The population in this study is all patients who was came in Public Health Center Mojoroto totaled 50 people. The sampling technique used is total sampling so the number of samples taken as many as 50 people.. Analysis for the effect of social group dynamics of events and healing tuberculosis lung disease is McNemar-Bowker Test. From the processing of the analysis statistic obtained probability value is more than 0.05, which means there is no effect of social group dynamics of events and healing tuberculosis lung disease in Public Health Center Mojoroto. The results showed no significant effect of group dynamics activity on the incidence of tuberculosis and cure of pulmonary tuberculosis. Most of sputum examination results before and after shown the negative result may caused by patients can not cough up sputum well.